The Investigation of Information Asymmetry’s Moderating Effect on the Relationship between Dividend Payments and Future Stock Price Crash Risk of Firms Listed on the Tehran Stock Exchange - Ghodratollah Talebnia; Maryam Metanat (بررسی‌های حسابداری و حسابرسی, 2018)
Objective: The purpose of this paper is to investigate the information asymmetry’s moderating effect on the Relationship between Dividend Payments and Future Stock Price Crash Risk of Firms Listed on the Tehran Stock Exchange (TSE). By evaluating the relationships, we tried to find out that whether the cash dividing payment will culminate in decreasing the crash risk of stock price or not. It is expected that in the absence of information asymmetry, the relation between divided payment and crash risk of stock price will change. Methods: In this regard, 155 companies were selected for the period of 2010 to 2014. The data from “Rahavard Novin” software, besides that, the financial statements data of the firms are based on TSE official website, the multivariate linear regression model and least squares method and panel data approach has been used to test research hypotheses. Results: The results of evaluations demonstrate a significant correlation between the cash dividend payment and the crash risk of future stock price of firms. However, asymmetry of information can not affect this correlation. Conclusion: Dividend payouts results in both decreasing free cash flow and external financing providing. Absorbing external cash flow results in monitoring of external suppliers on the performance of managers and firms and decline the crash risk of stock price. While there are significant correlations between asymmetry of information and each of the variables, the hypothesis of asymmetry of information as a Moderating variable (criterion) of this relation, was not confirmed.